Moderate penetrance genes complicate genetic testing for breast cancer diagnosis: ATM, CHEK2, BARD1 and RAD51D. (October 2022) - Graffeo, R.; Rana, H.Q.; Conforti, F.; Bonanni, B.; Cardoso, M.J.; Paluch-Shimon, S.; Pagani, O.; Goldhirsch, A.; Partridge, A.H.; Lambertini, M.; Garber, J.E.
Abstract: Breast cancer risk associated with germline likely pathogenic/pathogenic variants (PV) varies by gene, often by penetrance (high >50% or moderate 20–50%), and specific locus. Germline PVs in BRCA1 and BRCA2 play important roles in the development of breast and ovarian cancer in particular, as well as in other cancers such as pancreatic and prostate cancers and melanoma. Recent studies suggest that other cancer susceptibility genes, including ATM, CHEK2, PALB2, RAD51C and RAD51D confer differential risks of breast and other specific cancers. In the era of multigene panel testing, advances in next-generation sequencing technologies have notably reduced costs in the United States (US) and enabled sequencing of BRCA1/2 concomitantly with additional genes. The use of multigene-panel testing is beginning to expand in Europe as well. Further research into the clinical implications of variants in moderate penetrance genes, particularly in unaffected carriers, is needed for appropriate counselling and risk management with data-driven plans for surveillance and/or risk reduction. For individuals at high risk without any pathogenic or likely pathogenic variant in cancer susceptibility genes or some carriers of pathogenic variants in moderate-risk genes such as ATM and CHEK2, polygenic risk scores offer promise to help stratify breast cancer risk and guide appropriate risk management options. Cancer patients whose tumours are driven by the loss of function of both copies of a predisposition gene may benefit from therapies targeting the biological alterations induced by the dysfunctional gene e.g. poly ADP ribose polymerase (PARP) inhibitors and other novel pathway agents in cancers with DNA repair deficiencies. A better understanding of mechanisms by which germline variants drive various malignancies may lead to improvements in both therapeutic and preventive management options. Highlights: The interpretation of genetic testing results requires careful attention. ATM, CHEK2, RAD51D and BARD1 correlated with breast and other cancers risk. European and American guidelines discrepancies. Support European healthcare providers in interpreting and managing female carriers.